Identification of Ghrelin Receptor Blocker, D-[Lys3] GHRP-6 as a CXCR4 Receptor Antagonist - Patel, Kalpesh (Ivyspring International Publisher, 2011)
[D-Lys3]-Growth Hormone Releasing Peptide-6 (DLS) is widely utilized in vivo and in vitro as a selective ghrelin receptor (GHS-R) antagonist. Unexpectedly, we identified that DLS also has the ability to block CXCL12 binding and activity through CXCR4 on T cells and peripheral blood mononuclear cells (PBMCs). Moreover, as CXCR4 has been shown to act as a major co-receptor for HIV-1 entry into CD4 positive host cells, we have also found that DLS partially blocks CXCR4-mediated HIV-1 entry and propagation in activated human PBMCs. These data demonstrate that DLS is not the specific and selective antagonist as thought for GHS-R1a and appears to have additional effects on the CXCR4 chemokine receptor. Our findings also suggest that structural analogues that mimic DLS binding properties may also have properties of blocking HIV infectivity, CXCR4 dependent cancer cell migration and attenuating chemokine-mediated immune cell trafficking in inflammatory disorders.